Plant hormesis: The energy aspect of low and high-dose stresses - Elena A. Erofeeva (Plant Stress)
Hormesis is low-dose stimulation and high-dose inhibition. Various stressors (abiotic and biotic) can cause hormetic responses in plants. However, hormesis energy aspect remains insufficiently studied. This analysis examines the features of plant energy metabolism with high-dose (HDST) and low-dose (LDST) stressors. HDST cause significant damage and photoinhibition. Defense against HDST requires significant energy costs and, therefore, it is accompanied by a trade-off between growth and defense, as well as an increase in the dark respiration rate (the proportion of maintenance respiration increases). This can lead to negative energy budget (energy dissimilation exceeds energy assimilation) and a decrease in plant growth and productivity. LDST cause moderate damage. Defense against LDST does not require significant energy costs. Therefore, moderate defense activation eliminates damage and may increase photosynthesis and dark respiration efficiency. Apparently, both growth and maintenance components of dark respiration are increased. This leads to positive energy budget (energy assimilation exceeds energy dissimilation) and stimulates plant growth and productivity. Additionally, hormetic preconditioning increases plant resistance to HDST and prevents the significant energy loss to repair damage caused by HDST, thereby increasing yields. Notably, that only some doses of hormetic zone can optimize energy metabolism and increase plant productivity. This effect also depends on the development stage of stressed plants. The same stress signaling pathways (ABA, ROS signaling, etc.) may underlie changes in energy metabolism with HDST and LDST. Thus, these differences in plant energy metabolism with HDST and LDST should be accounted when conducting stress studies, including the development of DEB (Dynamic Energy Budget) models.